Body Image and Eating Disorders among Female Students: A Pilot Nutritional Psychology Study in Ghana - Comfort Nora Ntim; Jacob Owusu Sarfo (Centre for Behaviour and Wellness Advocacy, 2015)
Body image and eating disorders have emerged as an essential facet of bio-psychosocial well-being. Although considered less prevalent in Ghana than in the West, body image and eating disorders are issues of global concern. One hundred (100) female participants with a mean age of approximately 21 years were recruited after informed consent for this pilot study. Results showed a positive correlation between body image and eating disorders. In addition, there was no significant difference between the levels of university education on female body image and eating distortions in Ghana. These findings underscore the importance for more future studies in nutritional psychology and related clinical management.